2019
DOI: 10.1103/physrevlett.122.047701
|View full text |Cite
|
Sign up to set email alerts
|

Racemic Amino Acid Piezoelectric Transducer

Abstract: Single crystal L-amino acids can exhibit technologically useful piezoelectric and nonlinear optical properties. Here we predict, using density functional theory, the piezoelectric charge and strain and voltage tensors of the racemic amino acid DL alanine, and use the modeling data to guide the first macroscopic and nanoscopic piezoelectric measurements on DL-alanine single crystals and polycrystalline aggregates. We demonstrate voltage generation of up to 0.8 V from DL-alanine crystal films under simple manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 68 publications
(72 reference statements)
4
64
0
Order By: Relevance
“…In 2012, Lemanov 28 fired high frequency electrical pulses at crystalline amino acid powders (not single crystals) and found that DL-alanine and γ-glycine had the strongest piezoelectric response of the amino acids studied. This result is consistent with recent quantitative investigations into longitudinal piezoelectricity in these crystals, 26,29 which determined that both DL-alanine and γ-glycine crystallize in unique space groups that allow for a longitudinal d 33 constant of 10 pC/N. Lemanov did not detect piezoelectricity in L-cysteine or L-isoleucine powders, which are noncentrosymmetric in their single crystal form.…”
supporting
confidence: 90%
“…In 2012, Lemanov 28 fired high frequency electrical pulses at crystalline amino acid powders (not single crystals) and found that DL-alanine and γ-glycine had the strongest piezoelectric response of the amino acids studied. This result is consistent with recent quantitative investigations into longitudinal piezoelectricity in these crystals, 26,29 which determined that both DL-alanine and γ-glycine crystallize in unique space groups that allow for a longitudinal d 33 constant of 10 pC/N. Lemanov did not detect piezoelectricity in L-cysteine or L-isoleucine powders, which are noncentrosymmetric in their single crystal form.…”
supporting
confidence: 90%
“…62 The presence of longitudinal piezoelectricity in the l ‐amino acid film was well matched with density functional theory (DFT) calculations, and it was also found that there is a spontaneous polarization in the axial direction that could exhibit pyroelectric properties. In addition, they also in 2019 investigated the piezoelectricity of the racemic amino acid dl alanine 63. Since the sum of the dipole vectors in l ‐alanine is zero, there is no net polarization in the unit cell and no longitudinal piezoelectricity occurs.…”
Section: Piezoelectricity Of Amino Acidsmentioning
confidence: 99%
“…c) Crystal packing controls the orientation of alanine molecular dipoles (green arrows) in the unit cell, which determines the magnitude and direction of the corresponding piezoelectric responses. Reproduced with permission 63. Copyright 2019, American Physical Society.…”
Section: Piezoelectricity Of Amino Acidsmentioning
confidence: 99%
“…Our this is an order of magnitude greater than the g 33 value of <40 mV m N −1 for PZT [32,33] and is also greater than the predicted g 33 value of ∼480 mV m N −1 for a racemic alanine crystal [11] . As expected, the measured g 33 values are greater than those obtained for alkanethiol controls ( Figure S4, Supporting Information).…”
Section: Sams Of Thiol-containing Oligopeptides Ranging In Length Frmentioning
confidence: 57%
“…[2,6,7] In addition to well known piezoelectric polymers such as semi-crystalline poly(vinylidene fluoride) (PVDF), researchers have begun to develop fundamentally new piezoelectric materials such as helicenes, amino acids, viruses, and peptides. [5,[8][9][10][11][12] While the most commonly reported piezoelectric constant is the piezoelectric charge constant, d, the piezoelectric voltage constant, g, is perhaps more meaningful for sensing applications, since large voltages can be easily and accurately detected. [1,11,[13][14][15] Despite its importance, there are few examples of the voltage constant reported in the literature, making device comparisons difficult (see Guerin et al [15] and Chen et al [16] as examples).…”
mentioning
confidence: 99%